Polska Kronika Filmowa as a source for research on contemporary Polish architecture - Marciniak, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The materials used by architectural historians to research the post-war period are very limited, and the available archive resources are incomplete and dispersed. In this context, of special significance are other forms of visual materials that documented the spatial reality of the communist period. Documentary films, and in particular the Polska Kronika Filmowa [Polish Film Chronicle] newsreel, can make an an important contribution to and a resource for historical research on contemporary Polish architecture. This text contains methodological reflections on the role of film studying the history of contemporary architecture. It describes the new research options, including the ability to recreate original spatial phenomena, and also the contemporary techniques and technology as well as the educational dimension of the Polish Film Chronicle. In this context, it is especially interesting to compare the documentary material from the Chronicle with other archival material, e.g. drawings, plans and photographs. This method provides an additional opportunity for a fuller and more objective recreation of space in 3D. This “reverse modelling” can be used to restore or preserve the original condition of structures, or even to rebuild ones no longer existing.